Two new species of Xosopsaltria Kirkaldy, 1904, with a key to the species of South African pygmy bladder cicadas (Hemiptera: Cicadidae: Cicadettinae: Tettigomyiini) - Sanborn, Allen F.; Villet, Martin H. (Zootaxa, 2016)
Two species, Xosopsaltria brachyptera n. sp. and Xosopsaltria vitripennis n. sp., are described as new. Notes on their biology and a key to the South African pygmy bladder cicadas are also provided.